ASSESSING THE ENVIRONMENTAL IMPACT ON TOURISM DEVELOPMENT - Kamilova , Onabibi ("Science Shine" International scientific journal, 2024)
Abstract: This research examines the adoption and effectiveness of sustainable tourism strategies, with a specific focus on how they contribute to balancing economic advantages with environmental conservation. The research examines data from three diverse tourist locations known for their exceptional natural ecosystems to identify significant patterns in environmental effect resulting from different degrees of tourism activity. The results emphasize the essential requirement for incorporating integrated environmental management measures into tourist development in order to maintain ecological well-being while promoting economic expansion. The study offers empirically supported insights into the advantages of implementing sustainable practices that not only reduce negative environmental effects but also improve visitor experiences and local economic results.